Global Terrorism and Human Rights in Indonesia: Conflict Between Security and Freedom - Yessi Juwita lestari Saragih; Timbul Dompak; Karol Teovani Lodan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The escalation of global terrorism has posed substantial obstacles to the safeguarding of human rights globally. This study analyzes the intricate relationship between counter-terrorism strategies and human rights, highlighting how security policies may curtail individual liberties. This study conducts a comprehensive examination of several case studies to examine the effects of anti-terrorism laws and procedures in different nations. It further examines the intricate equilibrium that governments must sustain between safeguarding national security and preserving human rights norms. The study utilizes qualitative methodologies, encompassing document analysis and expert interviews in the domain. The findings indicate that although counter-terrorism initiatives are essential for public safety, they frequently lead to infringements of civil liberties, especially impacting underprivileged communities. The paper emphasizes the necessity of tackling these difficulties to guarantee that security measures do not excessively violate basic rights.The report concludes by recommending measures for policymakers to enhance human rights protections within counter-terrorism frameworks. Essential recommendations encompass promoting accountability and transparency in security operations while implementing equitable, non-discriminatory rules. Through the implementation of these measures, governments can proficiently counter terrorism while upholding fundamental human rights principles.